Super optical biosensors - Xiao, Caide (IOP (Series). Release 6., 2019)
Commencing by defining a set of standards for benchmarking sensors to enable better comparison, this book then proceeds to provide a review of the physics and workings of several optical and super optical biosensors, and introduces two more super optical biosensors, including the most sensitive super optical biosensor 'RMEPA', an abbreviation of three optical technique names: resonant mirroring, ellipsometry and attenuated total reflection. Mathcad is used to analyse these virtual biosensors and these codes and available to readers for use in their own research. It will be a key reference for researchers in academia and industry, particularly those involved in developing next generation optical biosensors. Part of IOP Series in Sensors and Sensor Systems.